Large-scale genome-wide association analysis of bipolar disorder identifies a new susceptibility locus near ODZ4 - Sklar, Pamela B.; Rietschel, Marcella; Strohmaier, Jana; Witt, Stephanie (Nature genetics, 2011)
We conducted a combined genome-wide association study (GWAS) of 7,481 individuals with bipolar disorder (cases) and 9,250 controls as part of the Psychiatric GWAS Consortium. Our replication study tested 34 SNPs in 4,496 independent cases with bipolar disorder and 42,422 independent controls and found that 18 of 34 SNPs had P < 0.05, with 31 of 34 SNPs having signals with the same direction of effect (P = 3.8 × 10−7). An analysis of all 11,974 bipolar disorder cases and 51,792 controls confirmed genome-wide significant evidence of association for CACNA1C and identified a new intronic variant in ODZ4. We identified a pathway comprised of subunits of calcium channels enriched in bipolar disorder association intervals. Finally, a combined GWAS analysis of schizophrenia and bipolar disorder yielded strong association evidence for SNPs in CACNA1C and in the region of NEK4-ITIH1-ITIH3-ITIH4. Our replication results imply that increasing sample sizes in bipolar disorder will confirm many additional loci.
*Psychiatric GWAS Consortium Bipolar Disorder Working Group: Pamela Sklar, Marcella Rietschel, Jana Strohmaier, Stephanie H. Witt [und 168 weitere Personen]
Gesehen am 18.10.2022
PDF enthält Corrigendum, veröffentlicht 29 August 2012, S. 986